(untitled) (Comprehensive Journal of Science, 2026)
The intelligences involve semantics—understanding the meaning of words. Also they involve phonology—the sounds and their interaction with each other and syntax—the syntactic rules, which allow teachers to engage students in problem solving and enables them to demonstrate understanding through performance assessment. In recent years, knowledge sharing has been identified as a major focus area for knowledge management. Efforts will be made to identify the most effective ways to share knowledge, as a step towards improving organizational performance. Various factors have been identified as impediments for knowledge sharing, including inadequate organizational structures, unfriendly organizational sharing cultures, and insufficient technological support in this striving. Gardner[1] sought to redefine the concept by incorporating recent findings from neuropsychology. He put forth the view that the intelligence quotient (IQ) does not adequately encompass the vast array of human abilities and that it misses important areas of intelligence. [1] Linguistic Intelligence refers to expressing and communicating ideas. This intelligence involves semantics—understanding the meaning of words; phonology—the sounds and their interaction with each other; and syntax—the rules governing the order of words and the pragmatic functions of different communications. Poets, writers, and attorneys are adept in linguistic intelligence. Musical Intelligence is the ability to hear, recognize, remember, and manipulate musical patterns. The first intelligence to emerge, often in early childhood, it involves an innate understanding of pitch (or melody), rhythm, and timbre (the characteristic qualities of a tone) and an ability to appreciate the emotional aspects of music. Logical-Mathematical Intelligence (nonverbal problem solving) is the capacity to move from the concrete to the abstract, to discern and make sense of patterns, symbols, and codes. This intelligence is the basis of the scientific, mathematical, and computer-oriented thinker. Spatial Intelligence is used in navigation, map reading, and the arts. Also called visual-spatial, it is the capacity to perceive the visual world accurately, to transform and modify initial perceptions, and to re-create aspects of these perceptions. Spatial intelligence is evident in artistically oriented individuals, such as visual artists, sculptors, and architects. The scientifically oriented person draws on spatial intelligence to study anatomy, geography, or topology. Bodily-Kinesthetic Intelligence (sports, drama, dance, and the use of tools) comprises the ability to use one’s body in highly skilled ways for expressive and goal-directed purposes. It includes the capacity to work well with objects, whether they involve fine motor skills or whole body movements. Dancers, performers (especially mimes), athletes, and craftspeople are accomplished in this intelligence. Interpersonal Intelligence (social and leadership skills) includes the ability to notice and make distinctions among other individuals, to read the intentions and desires of others, and to act on this social knowledge. This type of intelligence is important for political and religious leaders and is often well developed in skilled parents, teachers, and therapists. Intrapersonal Intelligence (self-awareness) involves an understanding of one’s own range of feelings and an ability to discriminate among them, label them, and draw upon them as a means of comprehending and guiding behavior. Novelists often tap into this intelligence, especially if they are also gifted in linguistic intelligence. Naturalist Intelligence is the ability to discriminate among living things and features of the natural world. The last of Gardner’s intelligences to be identified, it is characterized by an ability to recognize, distinguish, and categorize members of a species. Botanists and gardeners draw on this capacity.